Heavy metals modulate DNA compaction and methylation at CpG sites in the metal hyperaccumulator Arabidopsis halleri. (8th January 2021) - Galati, Serena; Gullì, Mariolina; Giannelli, Gianluigi; Furini, Antonella; DalCorso, Giovanni; Fragni, Rosaria; Buschini, Annamaria; Visioli, Giovanna
Abstract: Excess heavy metals affect plant physiology by inducing stress symptoms, however several species have evolved the ability to hyperaccumulate metals in above‐ground tissues without phytotoxic effects. In this study we assume that at subcellular level, different strategies were adopted by hyperaccumulator versus the non‐accumulator plant species to face the excess of heavy metals. At this purpose the comet assay was used to investigate the nucleoid structure modifications occurring in response to Zn and Cd treatments in the I16 and PL22 populations of the hyperaccumulator Arabidopsis halleri versus the nonaccumulator species Arabidopsis thaliana . Methy‐sens comet assay and RT‐qPCR were also performed to associate metal induced variations in nucleoids with possible epigenetic modifications. The comet assay showed that Zn induced a mild but non significant reduction in the tail moment in A. thaliana and in both I16 and PL22. Cd treatment induced an increase in DNA migration in nuclei of A. thaliana, whereas no differences in DNA migration was observed for I16, and a significant increase in nucleoid condensation was found in PL22 Cd treated samples. This last population showed higher CpG DNA methylation upon Cd treatment than in control conditions, and an up‐regulation of genes involved in symmetric methylation and histone deacetylation. Our data support the hypothesis of a possible role of epigenetic modifications in the hyperaccumulation trait to cope with the high Cd shoot concentrations. In addition, the differences observed between PL22 and I16 could reinforce previous suggestions of divergent strategies for metals detoxification developing in the two metallicolous populations.